A Research of Design Strategies of Elder-friendly Home Furniture for an Active Aging Society in Shanghai, China - Junli, Zhang (Universiti Malaysia Sarawak, 2024)
This research was conducted to respond actively to the social pressure brought by the ageing of China's population, and to respond to the smooth operation of China's "multi-level elderly service system based on the home, supported by the community and supplemented by institutions", to help the elderly with declining physical and mental functions to adapt to the existing living environment, extend independent and safe living, so as to realise ageing in place and respond to the expectation of an Active Ageing Society. Through field investigation, questionnaire survey, interview and observation in three Shanghai representative communities, markets and manufactures in Shanghai, complemented by design-based method, this research proposed the design and development strategies of Elderfriendly Home Furniture (EHF) from the perspective of an Active Ageing Society, includes dimension optimization, cabinet layout optimization, storage space optimization, safety and usability design, design for comfort, emotional design, economical design and standardized design. Finally, the above design approach was validated using the design-based validation method. It suggested establishing the correct social perception of Elder-friendly Home Furniture, activating and promoting the furniture market step by step, to guide the elderfriendly industry's steady growth. It hopes that this research could provide a reference and basis for future studies.